Comparative Sensitivities of Zooplankton to Ocean Acidification Conditions in Experimental and Natural Settings - Keil, Katherine E.; Klinger, Terrie; Keister, Julie E.; McLaskey, Anna K. (Frontiers in Marine Science, 2021)
Laboratory studies have demonstrated differential responses among zooplankton to conditions of low pH and high pCO2 that are associated with ocean acidification. We sought to evaluate these responses with specific reference to the inland waters of Puget Sound, Washington (USA) by comparing the results of experimental studies with field observations. We hypothesized that the relative sensitivities to pCO2 reported in the literature and revealed through meta-analysis would explain a significant amount of variation in zooplankton abundance in Puget Sound, where pH and pCO2 are known to vary across short spatial and temporal scales. To test this hypothesis, we collected zooplankton samples and environmental data on two research cruises in June and August 2017. We found that copepods, a highly sensitive taxon according to the meta-analysis, were consistently the most abundant taxon, while larvaceans, the least sensitive taxon according to the meta-analysis, reached high numbers in a few samples. Statistical analyses revealed that a combination of temperature, fluorescence, dissolved oxygen, and salinity was the primary determinant of zooplankton abundance at these stations during the two sampling periods. We found little association between empirical measures of station pH and the abundance of sensitive taxa as revealed by the meta-analysis, calling into question the coherence between laboratory and field studies, and suggesting that sensitivity to existing levels of ocean acidification may play a subordinate role in determining the abundance of some zooplankton taxa in this inland sea. The results of our study have important ramifications for long-term monitoring programs, especially with regard to the utility of measures of abundance as an indicator of response to environmental change.